Non‐invasive placentation in the marsupials Macropus eugenii (Macropodidae) and Trichosurus vulpecula (Phalangeridae) involves redistribution of uterine Desmoglein‐2. Issue 1 (15th January 2018) - Laird, Melanie K.; McShea, Hanon; Murphy, Christopher R.; McAllan, Bronwyn M.; Shaw, Geoff; Renfree, Marilyn B.; Thompson, Michael B.
Abstract : In mammalian pregnancy, the uterus is remodeled to become receptive to embryonic implantation. Since non‐invasive placentation in marsupials is likely derived from invasive placentation, and is underpinned by intra‐uterine conflict between mother and embryo, species with non‐invasive placentation may employ a variety of molecular mechanisms to maintain an intact uterine epithelium and to prevent embryonic invasion. Identifying such modifications to the uterine epithelium of marsupial species with non‐invasive placentation is key to understanding how conflict is mediated during pregnancy in different mammalian groups. Desmoglein‐2, involved in maintaining lateral cell–cell adhesion of the uterine epithelium, is redistributed before implantation to facilitate embryo invasion in mammals with invasive placentation. We identified localization patterns of this cell adhesion molecule throughout pregnancy in two marsupial species with non‐invasive placentation, the tammar wallaby ( Macropus eugenii ; Macropodidae), and the brushtail possum ( Trichosurus vulpecula ; Phalangeridae). Interestingly, Desmoglein‐2 redistribution also occurs in both M. eugenii and T. vulpecula, suggesting that cell adhesion, and thus integrity of the uterine epithelium, is reduced during implantation regardless of placental type, and may be an important component of uterine remodeling. Desmoglein‐2 also localizes to the mesenchymal stromal cells of M. eugenii and to epithelial cell nuclei in T. vulpecula, suggesting its involvement in cellular processes that are independent of adhesion and may compensate for reduced lateral adhesion in the uterine epithelium. We conclude that non‐invasive placentation in marsupials involves diverse and complementary strategies to maintain an intact epithelial barrier.